Risk Management in the Oil and Gas Industry : Offshore and Onshore Concepts and Case Studies - Da Ponte, Gerardo Portela, Jr (Gulf Professional Publishing, 2021)
"Risk Management in the Oil and Gas Industry: Offshore and Onshore Concepts and Case Studies delivers the concepts, strategies and good practices of offshore and onshore safety engineering that are applicable to petroleum engineering and immediately surrounding industries. Guided by the strategic risk management line, this reference organizes steps in order of importance and priority that should be given to the themes in the practical exercise of risk management activities, from the conceptual and design phase to operational and crisis management situations. Each chapter is packed with practical case studies, lessons learned, exercises, and review questions. The reference also touches on the newest techniques, including liquefied natural gas (cryogenics) operations and computer simulations that contemplate the influence of human behavior. Critical for both the new and experienced engineer, this book gives the best didactic tool to perform operations safely and effectively. Helps readers by presenting practical case studies and exercises that are included in every chapter Presents an understanding on how to approach and apply best practices specific to the oil and gas industry, both offshore and onshore Provides the knowledge needed to gain new techniques in computer simulation and human factors to apply to various sectors of the industry, including subsea and refineries." -- Publisher's description.